Ophthalmological assessment of preschool children: Eye blink and pupillary diameter - Lavezzo, Marcelo Mendes; Schellini, Silvana Artioli [UNESP] (My University, 2012)
Introduction: Nevertheless the eyes have a fast development mainly in the early childhood, there are many difficulties in eyes examination, leading to late diagnosis to various conditions. Conventional ophthalmic tests are difficult to implement in preschool children. Digital image processing system might provide important informations about the eyeblink and pupil evaluation. Purpose: To investigate, using a digital image processing system, the eyelid dynamics and the pupillary areas and diameters of normal preschool children. Methods: 50 newborns and 200 preschool children were examined. Images were recorded using a digital camera during three minutes. Complete and incomplete blink rates, opening, closing and complete blink times were calculated. Moreover, pupil diameter and pupil area of the preschool children were evaluated during attentive and spontaneous gaze. Data were expressed in pixels and arithmetic means of each parameter were calculated. Results: The complete eye blink was more common and the blink rate increased with age. The incomplete blink rate was the same for all ages. The eyelid opening and closing times and the complete blink time were similar for both sexes. The closing eyelid time was slower. The mean pupil diameter and area were similar for both eyes, presenting values of 18.5 and 311.7 pixels during attentive and 15.4 and 237.6 pixels during spontaneous gaze, respectively. There were no differences between sexes. However, six-year-old children showed lower pupil diameter and area. Conclusion: The digital image processing system is a very good method to evaluate children and permitted to observe the complete blink rate increases with age. Pupil diameter and area were larger during attention and similar for both eyes. © 2011 by Nova Science Publishers, Inc. All rights reserved.